Pengaruh Artificial Intelligence (AI) dan Leadership terhadap Sustainable Organisational Performance yang dimediasi oleh Employee Engagement pada Perusahaan E-commerce di Jakarta Selatan - Emilisa, Netania; Hilalluddin, Ahmad; Andrianto, Handika; Apriansyah, Hendri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of Artificial Intelligence (AI) and leadership on sustainable organizational performance, with employee engagement as a mediating variable, within e-commerce companies in South Jakarta. In the context of rapid digital transformation, the adoption of smart technologies such as AI and the implementation of adaptive leadership are considered critical drivers of long-term organizational sustainability. Employee engagement plays a central role in strengthening the link between AI implementation and leadership style with organizational performance outcomes. A quantitative research approach was employed using a survey method involving 150 respondents from various e-commerce firms. Data analysis was conducted using Structural Equation Modeling (SEM). The findings indicate that both AI and leadership significantly influence employee engagement and sustainable organizational performance. Moreover, employee engagement serves as a significant mediator in the relationship between AI and leadership and organizational sustainability. These results highlight the need for e-commerce companies to go beyond technology adoption and invest in effective leadership and employee engagement strategies to foster resilient and sustainable organizational outcomes.